2022
DOI: 10.3390/su14031408
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Education from Space: Using Satellite Earth Observation to Quantify Overcrowding in Primary Schools in Rural Areas of Nigeria

Abstract: Nigeria is a country with a rapidly growing youthful population and the availability of good quality education for all is a key priority in the sustainable development of the country. An important element of this is the need to improve access to high-quality primary education in rural areas. A key indicator for progress on this is the provision of adequate classroom space for the more than 20 million learners in Nigerian public schools because overpopulated classrooms are known to have a strong negative impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In contrast, precipitation observations serve as the primary input data required for SM modeling. However, all other products were inappropriate with respect to spatial and temporal variation of precipitation over the study area, with similar outcomes found in the previous findings of certain studies [37][38][39]. The temporal estimations of SM2Rain were in better agreement with gauge estimation, which is consistent with the findings of a particular study [10,24].…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, precipitation observations serve as the primary input data required for SM modeling. However, all other products were inappropriate with respect to spatial and temporal variation of precipitation over the study area, with similar outcomes found in the previous findings of certain studies [37][38][39]. The temporal estimations of SM2Rain were in better agreement with gauge estimation, which is consistent with the findings of a particular study [10,24].…”
Section: Discussionsupporting
confidence: 89%
“…Figure 14 depicts the assessment of four SPPs in terms of their ability to capture occurrence of precipitation events over the study area. Roebber [32] presented a performance diagram to graphically summarize the estimated values of the categorical indices (POD, SR, CSI, and Bias). The Roebber Performance Diagram (or simply performance diagram) was used in several previous investigations of SPPs in different countries [33].…”
Section: Ability Of Persiann Family Products To Capture the Amount Of...mentioning
confidence: 99%
“…It is essential to check their accuracy prior to their direct application [29]. Several scientists have evaluated the error characteristics of SPPs in many areas, including Africa [24,30], South America [25,31], Nigeria [32], Austria [6], China [33], Europe [12,25], Iran [17], India [10,34], United Arab Emirates [35], Taiwan [23], Brazil [36], and Pakistan [2,37,38]. Hamza et al [38] used both PERSIANN-CDR over the Hindukush Mountains along with other products (IMERG, TRMM and SM2-rain); he concluded that the PERSIAAN-CDR performance is more satisfactory then TRMM-3B42V7 and SM2Rain-ASCAT.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the usage of night-time satellite data can help monitor aspects of education facilities, such as access to electricity [182,183] and drinking water [184], which are closely linked to SDG 4.a.1 indicator (schools with basic service as electricity and internet). Furthermore, Andries et al [185] used VHR satellite data and enrolment data to calculate the primary school classroom area per pupil in rural Nigeria. They found that over 70% of the 1900 schools evaluated could be classified as overcrowded (according to Nigerian government metrics), this being highly correlated with poverty and literacy rates.…”
Section: Assessing Eo Contribution To Sdgs Indicators Using a Maturit...mentioning
confidence: 99%
“…They found that over 70% of the 1900 schools evaluated could be classified as overcrowded (according to Nigerian government metrics), this being highly correlated with poverty and literacy rates. Andries et al [185] also analysed their area per pupil result via the MMF approach, which characterised this EO support as partial for the SDG indicators 4.1.2. (Completion rate in primary education, lower secondary education, upper secondary education) and 4.6.1 (Proportion of population in each age group achieving at least a fixed level of proficiency in functional (a) literacy and (b) numeracy skills, by sex).…”
Section: Assessing Eo Contribution To Sdgs Indicators Using a Maturit...mentioning
confidence: 99%